1991
DOI: 10.1073/pnas.88.16.7219
|View full text |Cite
|
Sign up to set email alerts
|

T-cell receptor peptide immunization leads to enhanced and chronic experimental allergic encephalomyelitis.

Abstract: It has previously been reported that synthetic peptides correspondg to sequences derived from T-cell receptor variable regions identified as dominant in the T-cellmediated autoimmune disease experimental allergic encephalomyclitis in both the mouse and the rat can down-regulate disease in Lewis rats. In contrast to these results, we have found that immunization of Lewis rats with such peptides in complete Freund's adjuvant prior to induction of experimental allergic encephalomyelitis with myelin basic protein … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
20
0

Year Published

1994
1994
2000
2000

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 41 publications
(21 citation statements)
references
References 15 publications
1
20
0
Order By: Relevance
“…In close correlation with our data, the TcR peptide-mediated enhancement of EAE observed in this last work was manifested by an early onset of clinical signs and an increase in the severity and duration of EAE. Thus, in agreement with Desquenne-Clark et al [56] using the EAE model,we emphasize that this type of immunization is not a reliable method for inducing suppression of CIA.…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…In close correlation with our data, the TcR peptide-mediated enhancement of EAE observed in this last work was manifested by an early onset of clinical signs and an increase in the severity and duration of EAE. Thus, in agreement with Desquenne-Clark et al [56] using the EAE model,we emphasize that this type of immunization is not a reliable method for inducing suppression of CIA.…”
Section: Discussionsupporting
confidence: 92%
“…Our striking findings that the very same T cell clone reactive to CII possesses the potentiality to either enhance or suppress CIA are closely reminiscent of contradictory studies performed in two different groups using the EAE model. Indeed, Vandenbark et al [54] provided evidence of disease suppression in rats after immunization with a peptide of the CDR2-Vp8 region of the TcR specific for the MBP peptide 72-89 whereas Desquenne-Clark et al [56], using the same experimental system and peptide, observed an exacerbation of the disease. In close correlation with our data, the TcR peptide-mediated enhancement of EAE observed in this last work was manifested by an early onset of clinical signs and an increase in the severity and duration of EAE.…”
Section: Discussionmentioning
confidence: 97%
“…Subsequent to Offner et al's (1991) study with the Vp8 CDR2 peptide, Desquenne-Clark et al (1991) demonstrated that immunization with CDR2 peptide frequently led to enhancement of EAE, in contrast to the some sequence similarities between the EAE CP (to MBP 72-82) and TCR and MHC I1 molecules were found; but the physiological relevance of these similarity matches is not clear.…”
Section: Effect Of Eae Cp On Induction Of Eaementioning
confidence: 90%
“…Third, when the fragment is produced in subtolerogenic amounts by processing, the corresponding synthetic peptide will induce an immune response that could affect the cells naturally presenting this sequence, in the first place, the T cells expressing the appropriate receptor. When the latter cells are involved in autoimmune pathology, a response to them could modify the disease in two possible ways: downregulation with a beneficial effect (9,22), or upregulation leading to exacerbation (27). Future research will have to identify ways to direct the anti-TCR response toward beneficial effects.…”
Section: Discussionmentioning
confidence: 99%